Telephone speech enhancement for the hearing impaired - Tasnim, Bony; Murshed, C. Z. (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.